Innovation in Learning Balaghah: Optimization of Technology Media AZ Screen Recorder and YouTube in Enhancing Students' Appreciation of Adaby - Muhammad Afthon Ulin Nuha; Ahmad Fikri Amrullah; Nurul Musyafaah; Machrup Eko Cahyono; Murdiono (Arabiyatuna: Jurnal Bahasa Arab, 2026)
Balaghah science is a crucial branch of Arabic language studies that emphasizes linguistic beauty and effectiveness. However, traditional teaching methods often struggle to foster students' deep aesthetic appreciation (tadzawuq adaby). This study aims to optimize and evaluate the integration of AZ Screen Recorder and YouTube as technological learning media to enhance students' proficiency in Tadzawuq A daby. Method: Employing an explanatory sequential mixed-methods design, this research involved 90 students from the Arabic Language Education program at UIN Sayyid Ali Rahmatullah Tulungagung, divided equally into an experimental class (utilizing technology) and a control class (conventional method). Data were gathered through observations, interviews, and pretest-post-test assessments, and then analyzed using statistical parametric tests (Paired and Independent Sample T-Tests) alongside qualitative analysis. Results: The Independent samples T-Test revealed a statistically significant difference in post-test learning outcomes between the two groups (p = 0.012), with the experimental class achieving a substantially higher mean score (94.7) than the control class (85.1). Qualitative insights confirmed that the recorded materials provided learning flexibility and stimulated active, critical classroom discussions, though challenges such as unstable internet access persisted. Conclusion: Integrating AZ Screen Recorder and YouTube transcends mere theoretical mastery; it shifts the pedagogical paradigm by creating an interactive, independent, and dynamic learning environment that successfully elevates students' appreciation of literary aesthetics